Miltiply and Simplify. Assume that all variables are non-negitive...√3ab X √6ab^3?

√(3ab) X √(6ab^3)
= √(3ab*6ab^3)
= √(18a^2b^4)
= √(9a^2b^4 * 2)
= √(9a^2 b^4) * √(2)
= 3ab^2 * √(2)

This article contents is post by this website user, doesn't promise its accuracy.

More Questions & Answers...
  • Critique quote from ben franklin?
  • Calculus Problem?
  • Im writing a paper on Animal shelters?
  • What are some good 8th grade science fair ideas and projects?
  • MLA format?
  • Can anybody answer this questions about my homework?please i need it now...?
  • Can somebody simplify some polynomials for me?
  • Stupid Math RIddle HELP!?
  • Copyright 2006-2009 All Rights Reserved.